ANALYSIS OF THE IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION IN ENHANCING STUDENTS’ INTEREST AND LEARNING MOTIVATION IN THE IPAS SUBJECT IN CLUSTER 3 UNDER THE COORDINATION OF THE PANGGUL SUBDISTRICT, TRENGGALEK REGENCY - Nurhadi; Hikmah Eva Trisnantari; Ajar Dirgantoro (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the implementation of differentiated instruction in increasing students' interest and motivation in Science and Social Studies (IPAS) at Gugus 3, Panggul District, Trenggalek Regency. The research focuses on the aspects of implementation, strategies, and evaluation of instruction that accommodate student diversity. Using a descriptive qualitative approach, data were collected through observations, interviews, and questionnaires involving teachers and students within the Gugus 3 environment. Data analysis was conducted through reduction, display, and conclusion drawing. The results show that: (1) The implementation of instruction begins with accurate mapping of student needs through diagnostic assessment; (2) Content, process, and product differentiation strategies that integrate the local wisdom of the Panggul region significantly increase student interest (enjoyment and attention) and learning motivation (persistence and independence); (3) Process-based evaluation through constructive feedback is able to maintain the consistency of students' intrinsic motivation. In conclusion, differentiated instruction is a strategic key in creating inclusive and meaningful IPAS learning at the elementary school level